The Enhancement of Students’ Speaking Skills through Project-Based Learning in Non-Formal Education - Hidayati, Dini; Siahaan, Leroy Holman; Andriani, Novi; Putri , Firsta Malyda (UNIB Press, 2024)
This study examines how Project-Based Learning (PBL) improves speaking skills in Paket C students at PKBM Kota Bekasi, an Indonesian non-formal education institution. This research aims to design and deploy customised PBL materials for these children and evaluate their effectiveness in boosting student involvement, communication, and speaking proficiency. To assess PBL's impact, the study uses mixed methods, including qualitative and quantitative methods. Fluency, coherence, and pronunciation improvements are assessed pre- and post-intervention to acquire quantitative data. Student interviews, classroom observations, and professional evaluations provide qualitative insights into student involvement and motivation. PBL greatly improves pupils' speaking fluency, coherence, and pronunciation. Students are more motivated and engaged in learning than using traditional approaches. PBL's interactive and collaborative character creates a dynamic learning environment that fosters active engagement and language skill application. However, the report also finds significant PBL implementation problems. These include restricted technology resources, which affects project delivery and execution, and the necessity for educators to change their teaching practices to enable PBL. Positive results imply that PBL may be an effective pedagogical technique for resolving educational gaps in non-formal settings, despite these challenges. The research shows educators and policymakers that PBL can improve non-formal education learning. Future study should design cost-effective PBL models that handle resource constraints and examine PBL's long-term effects on students' academic and professional growth. Keywords: Curriculum Development, Paket C, PKBM, Project-Based Learning, Speaking Skills